Prevalence and Determinant Factors Affecting the Mental Health of Diabetes Mellitus Patients in Lamongan Regency, Indonesia - Abdul Rokhman; Nur Hidayati; Dadang Kusbiantoro (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes mellitus is one of the most prevalent chronic diseases worldwide, who are at a higher risk of developing psychological issues instead of physical complications. Objective to analyze the prevalence and determinant factors associated with mental health issues among diabetes patients. This cross-sectional study involving 71 diabetes mellitus patients in Lamongan Regency between May and August 2023. Data were analyzed using Spearman’s test and logistic regression (α ≤ 0.05). Among the participants, 71.8% were female, 47.9% were aged 55–65 years, and 83.1% were non-smokers. Spearman’s test results indicated no significant association between diabetes type, history of heart disease, history of hypertension, and health insurance status with mental health issues (p = 0.057, p = 0.693, p = 0.925, p = 0.544). However, a significant association was found between physical activity and mental health issues in diabetes patients (p = 0.045). Physical activity was identified as the dominant factor influencing the risk of mental health issues among diabetes patients (p = 0.028, 95% CI = 8.812 [1.267–61.317]). Diabetes patients who engage in strenuous physical activity are eight times more likely to experience mental health issues compared to those engaging in light physical activity.